Performance Enhancement In Higher Education Through Optimization Of Internal Audit Functions - Nur Ravita Hanun; Hadiah Fitriah; Detak Prapanca (Jurnal Akademi Akuntansi, 2022)
This research is based on the rapid development of Higher Education in Muhammadiyah, but the internal supervision of universities had been not optimal yet. So this study aims to explore the implementation and function of Internal Audit in Muhammadiyah University. This research uses qualitative methods with a case study approach. The data collection process is carried out through interviews, Focus Group Discussions (FGDs) and documentation. Data analysis is conducted with Nvivo software. The informants in this study were the Head of the Internal Supervisory Unit (SPI) and the Head of the University Financial Administration Board from 3 (three) Muhammadiyah Universities (PTM). The results of this study show that the role of internal audit is to ensure efficiency and effectiveness in managing higher education operational. Currently, the internal function of the auditor is not only as a monitor (watchdog) but also as a consultant and catalyst for improving the performance of universities.